Pengaruh Functionality Terhadap Kesuksesan Produk - Fitri Trapsilawati; Subagyo . (Faculty of Engineering, Universitas Gadjah Mada, 2010)
AbstractThis study was done for analyzing relation between product functionality and success of a product. Product functionality data of 58 different products were used in this study. The data of products were taken from different types of industry, i.e.: automotive, telecommunication, electronic and service. The result showed that the relation between product functionality andsuccess of a product tends to form “must-be” type of Kano diagram. Therefore, in designing a product, producers should not add more “value” in functionality.Keywords: functionality, Kano diagram, success of a product.